2010
DOI: 10.4049/jimmunol.0903168
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate Oxidation Acidifies Endosomes, Regulating Antigen Processing and TLR9 Signaling

Abstract: Material

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 50 publications
(63 reference statements)
1
17
0
Order By: Relevance
“…In fact, CGD favors vesicular acidification and increased conventional antigen proteolysis [35]. In sharp contrast, GlyAg processing is dependent upon a neutral pH and acidification stops GlyAg processing in cells [40]. As a result, one might expect the CGD cells to process GlyAg less than the WT counterparts due to increased acidification, yet we observed the opposite.…”
Section: Discussionmentioning
confidence: 74%
“…In fact, CGD favors vesicular acidification and increased conventional antigen proteolysis [35]. In sharp contrast, GlyAg processing is dependent upon a neutral pH and acidification stops GlyAg processing in cells [40]. As a result, one might expect the CGD cells to process GlyAg less than the WT counterparts due to increased acidification, yet we observed the opposite.…”
Section: Discussionmentioning
confidence: 74%
“…In order to confirm the causal relationship between NO and suppression, we examined MDSC suppressive activity using the iNOS inhibitor 1400W (40,41). Directly inhibiting NO production (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Because successful cleavage of TLR9 required an acidic compartment, it is tempting to speculate that uptake of Af conidia and subsequent phagosomal acidification (41) may facilitate cleavage and retention in the phagosome. A recent report indicated that acidification induced by carbohydrates from encapsulated microbes facilitated TLR9 signaling (49). TLR9 recruitment, cleavage and retention at the fungal phasosome may be prerequisite steps for successful signaling to TLR9 ligands that are released during phagosomal processing.…”
Section: Discussionmentioning
confidence: 99%